The Significance of Indonesia's Extradition Efforts in Retrieving the Proceeds of Corrupt Crimes Carried Out by Firms that Entered the Nation with Legal Assistance - ., Jufri; Danil, Elwi; Yunara, Edi; Sukarja, Detania (Journal of Ecohumanism, 2024)
The prevalence of certain types of crime, such as corporate corruption offenses, has an impact on economic advancement. Money that dishonest people pilfer is frequently stashed abroad. According to national and international laws, the study addresses the significance of Indonesia's extradition cooperation in the return of criminal assets and corrupt individuals who cross national borders. An approach to this research is normative jurisprudence. According to research, dishonest individuals in Indonesia are transferring pilfered goods overseas in order to conceal and safeguard their holdings. It was determined that mutual legal assistance, or MLA, obtained through an extradition agreement, is a crucial legal tool that Indonesia uses to enforce the law enforcement process against corporate corruption crimes that cross national borders in order to track down offenders and seize corrupt assets. Act No. 1 of 2006, however, only addresses mutual assistance in criminal cases. It is anticipated that by enhancing the criminal, civil, and administrative facets, Indonesian domestic MLA legislation will be reinforced. in order to improve the handling of corruption and safeguard victims.